A Study of Tea Production From Liberica Green Coffee Skin in Tungkal, Jambi as a Refreshing Drink - Emanauli; Prihantoro, Rudi (Department of Technology of Agricultural product (THP) Jambi University, 2018)
Coffea Liberica is a coffee plant that grow at lowlands and specifically on peatlands. Unlike Arabica and Robusta, Liberica coffee is large and able to grow up to 9 meters in height. Tea as a refreshing drink made from coffee skin which called cascara tea, had been developed in Indonesia and around the world. However, tea that made from green coffee skin is rarely been produced. This study used vary drying temperature (70, 80, 90â„ƒ) and time (12, 18, 24 hours). Refreshing drink products had a yellowish brown color with a hint of bitterness and tea leaves aroma. Drying condition with temperature of 90â„ƒ and 12 hours of time duration is resulted in the most preferred beverage. The dried green coffee skin had 5.73% moisture content, 12.58% crude fiber, 4.78% ash content, pH 3.8, 9.95 of total polyphenols and 86.08 of antioxidant content.